2017
DOI: 10.3390/nu9070746
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Effects of Flavanol-Containing Tea, Cocoa and Apple Products on Body Composition and Blood Lipids: Exploring the Factors Responsible for Variability in Their Efficacy

Abstract: Several randomized controlled trials (RCTs) and meta-analyses support the benefits of flavanols on cardiometabolic health, but the factors affecting variability in the responses to these compounds have not been properly assessed. The objectives of this meta-analysis were to systematically collect the RCTs-based-evidence of the effects of flavanol-containing tea, cocoa and apple products on selected biomarkers of cardiometabolic risk and to explore the influence of various factors on the variability in the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 172 publications
(156 reference statements)
2
45
2
1
Order By: Relevance
“…It is thus difficult to attribute the beneficial effects to a particular compound(s). In this regard, some studies have been conducted with polyphenol-rich berry products in comparison with nutrient-matched controls to try to associate the polyphenols intake with the response of the individuals [30]. Also, the association between the intake of ET-containing pomegranate products and the effects on cardiometabolic risk factors has been investigated with some evidence of a potential link between responses and specific ET-derived metabolites, but the effects of other constituents of these products have not been fully discarded [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…It is thus difficult to attribute the beneficial effects to a particular compound(s). In this regard, some studies have been conducted with polyphenol-rich berry products in comparison with nutrient-matched controls to try to associate the polyphenols intake with the response of the individuals [30]. Also, the association between the intake of ET-containing pomegranate products and the effects on cardiometabolic risk factors has been investigated with some evidence of a potential link between responses and specific ET-derived metabolites, but the effects of other constituents of these products have not been fully discarded [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Although the changes in lifestyle and diet are still considered as the most significant, many data suggest that increased dietary intake of antioxidants is a crucial factor in the prevention of NCDs [ 9 , 10 , 11 , 12 ]. Among many secondary metabolites of plant origin, polyphenols are the most abundant and nutritionally significant ones, possessing a wide spectrum of biological activities [ 13 ]. Because of the significant concentration of catechins (flavan-3-ols) and high daily intake (estimated at 120 mL/person/day), tea infusions are recently considered as the major sources of these chemicals for a general population [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The meta-analysis on flavanols also confirmed that they beneficially modulate several cardiometabolic risk factors, such as plasma lipids, BMI and waist circumference. However, higher efficacy was demonstrated in the participants with BMI ≥ 25 kg/m 2 and in non-medicated individuals, revealing the inter-individual variability (117) . Similarly, the beneficial effects of ellagitannins and anthocyanins on selected cardiometabolic risk factors were found to be more prominent in overweight and obese subjects (118) , and the effects of hydroxycinnamic acids may be greater in individuals at higher cardiometabolic risk (119) .…”
Section: Human Intervention Studiesmentioning
confidence: 90%